2002
DOI: 10.1098/rspb.2001.1875
|View full text |Cite
|
Sign up to set email alerts
|

Nominal kinship cues facilitate altruism

Abstract: We investigated whether names in common promote altruistic behaviour, predicting that this would be especially so for relatively uncommon names, for surnames (which are better kinship cues than ® rst names), and among women (who, although less willing than men to help strangers, according to prior research, are also the primary`kin keepers' ). We solicited help from 2960 email addressees, with the request ostensibly coming from a same-sex person sharing both, either, or neither of the addressee's ® rst and las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 27 publications
6
26
0
1
Order By: Relevance
“…Consistent with our findings, Burger et al, [21] also found that the effect of similarity on compliance was only observed when the incidental similarity shared by the participants with someone was uncommon. The same results were found by Oates and Wilson [23] who investigated whether having names in common promotes altruistic behavior in a computer mediated communication by sending e-mail requests to people on the Web. They found that sharing a first name with someone is associated with greater helping behavior (obtaining some information about the city's sports team mascot) then when no similarity existed.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Consistent with our findings, Burger et al, [21] also found that the effect of similarity on compliance was only observed when the incidental similarity shared by the participants with someone was uncommon. The same results were found by Oates and Wilson [23] who investigated whether having names in common promotes altruistic behavior in a computer mediated communication by sending e-mail requests to people on the Web. They found that sharing a first name with someone is associated with greater helping behavior (obtaining some information about the city's sports team mascot) then when no similarity existed.…”
Section: Discussionsupporting
confidence: 67%
“…Results showed that compliance to the request was significantly higher in the same surname condition than in the different surname condition, and that the delay in response was significantly shorter in the same surname condition than in control condition. Oates and Wilson [23] found the same effect when using a similar first name between the sender and the receiver. Such results are in keeping with Heider [24] who proposed that incidental similarities create a sense of association between people.…”
Section: Similarity and Mimicrysupporting
confidence: 52%
“…Doing so requires using a methodology in which perceivers are presented with previously unknown nonkin targets. Evidence supporting the hypothesized cue-based kin-recognition process can be obtained if perceivers respond more positively to targets displaying the hypothesized cue than to targets not displaying the cue (e.g., DeBruine, 2002;Oates & Wilson, 2002). However, evidence of a more affectively positive response by itself cannot unequivocally support the activation of psychological mechanisms pertaining to kinship.…”
Section: Overview Of the Present Studymentioning
confidence: 90%
“…People may be attentive to additional superficial similarities as kinship cues. For instance, people are more likely to assist someone who shares their name or has similar fingerprints, especially if the shared feature is perceived as uncommon (Burger, Messian, Patel, del Prado, & Anderson, 2004;Oates & Wilson, 2002).…”
Section: Proximate Mechanisms Of Nepotistic Discriminationmentioning
confidence: 99%
“…Daarom wordt het paradigma waarmee de recente ontwikkelingen in de gcn-wetenschappen kunnen worden samengevat, in eigen land, ook wel het paradigma van het 'slimme onbewuste' genoemd . Of, in onderscheid van het freudiaanse onbewuste, het 'adaptief onbewuste' of het 'nieuwe onbewuste' (Wilson 2002). Anders dan het freudiaanse onbewuste toont het nieuwe onbewuste zich niet slechts zo nu en dan in versprekingen, maar reguleert het onze dagelijkse interactie met elkaar en de wereld diepgaand op een adaptieve en efficiënte manier.…”
Section: Zelfbeeld Versus Wetenschapunclassified